2018
DOI: 10.2147/amep.s180526
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the impact of national education in pediatric palliative care: the Quality of Care Collaborative Australia

Abstract: PurposeThe Quality of Care Collaborative Australia (QuoCCA) provided pediatric palliative care education across Australia with the aim of improving the quality of services. The education was delivered through a collaboration of six tertiary pediatric palliative care services, through funding for Nurse Educators, Medical Fellows, a National Allied Health Educator, and national project staff.MethodsPre- and post-education surveys were completed by participants immediately following the education, and confidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 31 publications
3
30
0
Order By: Relevance
“…1 The top learning needs were used to develop the QuoCCA continuous practice development curriculum, and ongoing evaluation and refinement achieved national harmonization of the curriculum. 2 For the first three-year round of funding, 337 education sessions were completed around Australia by QuoCCA funded educators based in tertiary PPC services in Brisbane, Melbourne, Adelaide and Perth; involving 767 hours of education and 5773 participants. Regional and remote locations received 40% of the QuoCCA education sessions.…”
Section: Introductionmentioning
confidence: 99%
“…1 The top learning needs were used to develop the QuoCCA continuous practice development curriculum, and ongoing evaluation and refinement achieved national harmonization of the curriculum. 2 For the first three-year round of funding, 337 education sessions were completed around Australia by QuoCCA funded educators based in tertiary PPC services in Brisbane, Melbourne, Adelaide and Perth; involving 767 hours of education and 5773 participants. Regional and remote locations received 40% of the QuoCCA education sessions.…”
Section: Introductionmentioning
confidence: 99%
“…The core aims of QuoCCA were to improve the capability of national HPs, improve access to and quality of PPC, and increase community awareness of death and dying in the pediatric population. 13 We believe QuoCCA has enabled transformative learning and enabled social action in the context of PPC through these innovative teaching and learning methods.…”
Section: Discussionmentioning
confidence: 99%
“…The QuoCCA project enabled funding of dedicated medical, nursing, and allied health educators who improved the knowledge and capability of HPs providing PPC throughout Australia. 13 Although the QuoCCA program was set up to increase capability through an education framework, the study revealed other positive outcomes that supported staff: the development of partnerships between services, mentoring of staff by specialist services, sustaining staff well-being, and learning from children and families. Traditional education programs worldwide are incorporating models of individual and team mentorship as a way of increasing workforce capability and resilience.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations